Phylogenomics and Morphological Reconstruction of Arcellinida Testate Amoebae Highlight Diversity of Microbial Eukaryotes in the Neoproterozoic - Lahr, Daniel J G; Kosakyan, Anush; Lara, Enrique; Mitchell, Edward A D; Morais, Luana; Porfirio-Sousa, Alfredo L; Ribeiro, Giulia M; Tice, Alexander K; Pánek, Tomáš; Kang, Seungho; Brown, Matthew W (Current biology, 2019)
Life was microbial for the majority of Earth's history, but as very few microbial lineages leave a fossil record, the Precambrian evolution of life remains shrouded in mystery. Shelled (testate) amoebae stand out as an exception with rich documented diversity in the Neoproterozoic as vase-shaped microfossils (VSMs). While there is general consensus that most of these can be attributed to the Arcellinida lineage in Amoebozoa, it is still unclear whether they can be used as key fossils for interpretation of early eukaryotic evolution. Here, we present a well-resolved phylogenomic reconstruction based on 250 genes, obtained using single-cell transcriptomic techniques from a representative selection of 19 Arcellinid testate amoeba taxa. The robust phylogenetic framework enables deeper interpretations of evolution in this lineage and demanded an updated classification of the group. Additionally, we performed reconstruction of ancestral morphologies, yielding hypothetical ancestors remarkably similar to existing Neoproterozoic VSMs. We demonstrate that major lineages of testate amoebae were already diversified before the Sturtian glaciation (720 mya), supporting the hypothesis that massive eukaryotic diversification took place in the early Neoproterozoic and congruent with the interpretation that VSM are arcellinid testate amoebae.
Keywords: ancestral state reconstruction; Lobosea; Arcellinida classification; vase-shaped microfossils; phylogenomics; Neoproterozoic; zkameněliny; protozoální geny; Phylogeny; Fossils; fylogeneze; arcellinida; Genes, Protozoan